2010
DOI: 10.1371/journal.pone.0010652
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Gene RanBPM Functions in the Mushroom Body to Regulate Larval Behavior

Abstract: BackgroundIn vertebrates, Ran-Binding Protein in the Microtubule Organizing Center (RanBPM) appears to function as a scaffolding protein in a variety of signal transduction pathways. In Drosophila, RanBPM is implicated in the regulation of germ line stem cell (GSC) niche organization in the ovary. Here, we addressed the role of RanBPM in nervous system function in the context of Drosophila larval behavior.Methodology/Principal FindingsWe report that in Drosophila, RanBPM is required for larval feeding, light-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Insulin signalling regulates starvationdependent food intake behaviour in the Drosophila larva (Britton et al, 2002;Wu et al, 2005a;Wu et al, 2005b). Our previous work indicated that the mushroom body plays a role in larval feeding behaviour (Scantlebury et al, 2010). Therefore, we asked whether proper insulin signalling is required in mushroom body neurons for feeding behaviour during larval development.…”
Section: Reduced Insulin Signalling In Mushroom Body Neurons Impairs mentioning
confidence: 97%
See 1 more Smart Citation
“…Insulin signalling regulates starvationdependent food intake behaviour in the Drosophila larva (Britton et al, 2002;Wu et al, 2005a;Wu et al, 2005b). Our previous work indicated that the mushroom body plays a role in larval feeding behaviour (Scantlebury et al, 2010). Therefore, we asked whether proper insulin signalling is required in mushroom body neurons for feeding behaviour during larval development.…”
Section: Reduced Insulin Signalling In Mushroom Body Neurons Impairs mentioning
confidence: 97%
“…RanBPM is highly expressed in the cytoplasm of the mushroom body neurons and is also expressed to a lesser degree in a large number of central nervous system neurons (Scantlebury et al, 2010). Targeted expression of RanBPM in the mushroom body rescues the feeding behaviour and growth phenotypes of RanBPM mutant larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Other sensory projections are ipsilateral. While a majority of sensory neurons extend their axons through a ventral nerve root, the dorsal bd (dbd) neurons send their axons through a dorsal nerve root (Schrader & Merritt ; Grueber et al . ).…”
Section: Anatomy and Development Of Sensory Feedback Neuronsmentioning
confidence: 99%
“…Each class of sensory neurons, representing different modalities, projects axons to distinct areas within the CNS to make connections to second‐order neurons (Fig. B) (Merritt & Whitington ; Schrader & Merritt ; Zlatic et al . ; Grueber et al .…”
Section: Anatomy and Development Of Sensory Feedback Neuronsmentioning
confidence: 99%
See 1 more Smart Citation